Porous Organic Polymers: An Emerged Platform for Photocatalytic Water Splitting - Xu, Chen; Zhang, Weijie; Tang, Juntao; Pan, Chunyue; Yu, Guipeng (Frontiers in Chemistry, 2018)
Porous organic polymers (POPs), known for its high surface area and abundant porosity, can be easily designed and constructed at the molecular level. The POPs offer confined molecular spaces for the interplay of photons, excitons, electrons and holes, therefore featuring great potential in catalysis. In this review, a brief summary on the recent development of some current state-of-the-art POPs for photocatalytic water splitting and their design principles and synthetic strategies as well as relationship between structure and photocatalytic hydrogen or oxygen evolution performance are presented. Future prospects including research directions are also proposed, which may provide insights for developing POPs for photocatalytic water splitting with our expectations.